Avaliação do desempenho higrotérmico de habitações de interesse social em Santa Maria/RS - Linck, Gabriela Inês (2013)
In Brazil the insufficient investments in public politics on low income housing (LIH) and the urgency in solve the great housing deficit contribute to the low building quality of the housing, which historically presents problems regarding thermal comfort and energy efficiency. The occupants are the most affected with this practice, since, in order to improve their thermal comfort, they must use artificial conditioning, which is incompatible with their incomes. This research aims to evaluate the hygrothermal performance of single-family one-floor low income housing typologies in use located in Santa Maria, southern Brazil and the thermal comfort of occupants. For this study, houses under several solar orientations were selected in three different locations of the city. The method used for the evaluation of the performance is based in requirements and criteria obtained from the mathematic calculation of thermal parameters which consider the building performance in a global basis, such as the global heat flow coefficients, the radiant asymmetry, among others. Based on the results obtained, the houses can be classified according to the achieved performance. Furthermore, the perceived thermal sensation was evaluated through the application of a questionnaire during the winter and summer periods of 2012. The satisfaction degree was assessed according the Predicted Mean Vote (PMV) proposed by Fanger and standardized by the International Organization for Standardization 7730 (ISO, 1994) and the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE, 2004). While questionnaires were applied, indoor and outdoor air temperatures and relative humidity were measured to compare against the opinion of the interviewees. Results show that the evaluated houses present a very unsatisfying hygrothermal performance as they do not show building envelopes compatibles with the local climate. Among all the evaluated houses, those from the Residencial Zilda Arns presented best performance due to the higher thermal resistance of the roof and the possibility of ventilation. Regarding the results of the survey, the calculated hygrothermal performance reflects the opinion of the interviewees, who consider their houses thermally uncomfortable for both winter and summer. The rooms pointed as the most uncomfortable have unfavourable solar orientation a either during the summer or during the winter. Interviewees pointed the cover as the main responsible for the thermal exchanges. Besides, the low constructive quality of the housings is noted through the high and low temperatures measured during the summer and the winter.